(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the effect of casein to fat ratios (0.68, 0.72, and 0.76) on the functional properties of Prato cheese at 2, 15, 30, and 45 days of ripening. The different ratios did not interfere with the physicochemical characteristics, pH, Aw, proteolysis indices, color parameters, sliceability and sensory profile of the cheeses among the treatments. However, pH, proteolysis indices, texture profile, L* and b* color parameters of the cheeses changed through the ripening time. The cheeses made from milk standardized to casein/fat ratio of 0.68 presented lower chewiness values. The casein to fat ratio of 0.68 increased the protein and fat recoveries, and provided greater meltability and greater formation of free oil when compared to cheeses made from milk with casein to fat ratio of 0.76. Therefore, casein to fat ratio of 0.72 is recommended for the production of Prato cheese as the cheese presents good functional properties at this value, such as intermediate melting and chewiness, and less release of free oil.